Answer:
25.6 units
Step-by-step explanation: From the figure we can infer that our triangle has vertices A = (-5, 4), B = (1, 4), and C = (3, -4).
First thing we are doing is find the lengths of AB, BC, and AC using the distance formula:
d=\sqrt{(x_2-x_1)^{2} +(y_2-y_1)^{2}}
where
(x_1,y_1) are the coordinates of the first point
(x_2,y_2) are the coordinates of the second point
- For AB:
d=\sqrt{[1-(-5)]^{2}+(4-4)^2}
d=\sqrt{(1+5)^{2}+(0)^2}
d=\sqrt{(6)^{2}}
d=6
- For BC:
d=\sqrt{(3-1)^{2} +(-4-4)^{2}}
d=\sqrt{(2)^{2} +(-8)^{2}}
d=\sqrt{4+64}
d=\sqrt{68}
d=8.24
- For AC:
d=\sqrt{[3-(-5)]^{2} +(-4-4)^{2}}
d=\sqrt{(3+5)^{2} +(-8)^{2}}
d=\sqrt{(8)^{2} +64}
d=\sqrt{64+64}
d=\sqrt{128}
d=11.31
Next, now that we have our lengths, we can add them to find the perimeter of our triangle:
p=AB+BC+AC
p=6+8.24+11.31
p=25.55
p=25.6
We can conclude that the perimeter of the triangle shown in the figure is 25.6 units.
Read more on Brainly.com - brainly.com/question/12560433#readmore
Number of Payments per year (y) = 12
Number of Payments (n) = 36
Total Interest (c) = $158.15
PLEASE HELP!!!!
Step-by-step explanation:
Answer:
0.3? because it's one 0 and so you move it once, to the left
Given that, the length of the garden is 2(x+6)feet and width is 3.5x feet.
So, length : l = 2(x+6) and width = 3.5x.
To find the fence of the garden we need to find the perimeter of the rectangle.
Formula to find the perimeter is:
p = 2l + 2b
= 2*2(x+6) + 2*3.5x
= 4(x+6) + 7x By multiplication.
= 4x + 24 + 7x By distribution property.
= 11x + 24 Combining the like terms.
So, he need to buy 11x + 24 feet fencing.
Hope this helps you!
Yes, both the expressions are equivalent.
An expression in maths is a sentence with a minimum of two numbers or variables and at least one maths operation. This maths operation can be addition, subtraction, multiplication, or division.
Given that, x/3 is equivalent to 1/3x, yes or not?
So, we can write x/3 as
1/3×x
= x/3
Since, either you multiply by 1/3 or divide by 3 both are same thing,
1/3×x = x/3 = 0.333x
for example; 4÷2 = 2 or 4×1/2 = 2, in both case the answer is same, that means the expression given are also equal.
Hence, we can conclude both the expressions are equivalent.
For more references on expressions, click;
#SPJ2